A three-dimensional LUR framework for PM2.5 exposure assessment based on mobile unmanned aerial vehicle monitoring. (15th May 2022) - Xu, Xiangyu; Qin, Ning; Zhao, Wenjing; Tian, Qi; Si, Qi; Wu, Weiqi; Iskander, Nursiya; Yang, Zhenchun; Zhang, Yawei; Duan, Xiaoli
Abstract: Land use regression (LUR) models have been widely used in epidemiological studies and risk assessments related to air pollution. Although efforts have been made to improve the performance of LUR models so that they capture the spatial heterogeneity of fine particulate matter (PM2.5 ) in high-density cities, few studies have revealed the vertical differences in PM2.5 exposure. This study proposes a three-dimensional LUR (3-D LUR) assessment framework for PM2.5 exposure that combines a high-resolution LUR model with a vertical PM2.5 variation model to investigate the results of horizontal and vertical mobile PM2.5 monitoring campaigns. High-resolution LUR models that were developed independently for daytime and nighttime were found to explain 51% and 60% of the PM2.5 variation, respectively. Vertical measurements of PM2.5 from three regions were first parameterized to produce a coefficient of variation for the concentration (CVC) to define the rate at which PM2.5 changes at a certain height relative to the ground. The vertical variation model for PM2.5 was developed based on a spline smoothing function in a generalized additive model (GAM) framework with an adjusted R 2 of 0.91 and explained 92.8% of the variance. PM2.5 exposure levels for the population in the study area were estimated based on both the LUR models and the 3-D LUR framework. The 3-D LUR framework was found to improve the accuracy of exposure estimation in the vertical direction by avoiding exposure estimation errors of up to 5%. Although the 3-D LUR-based assessment did not indicate significant variation in estimates of premature mortality that could be attributed to PM2.5, exposure to this pollutant was found to differ in the vertical direction. The 3-D LUR framework has the potential to provide accurate exposure estimates for use in future epidemiological studies and health risk assessments. Graphical abstract: Image 1 Highlights: LUR models for daytime and nighttime explained 51% and 60% of the variation in PM2.5 . Adjusted R 2 of vertical variation model is 0.91, explaining 92.8% of the variance. 3-D LUR framework revealed differences in PM2.5 exposure in the vertical direction. The differences between the 3-D and 2-D LUR estimation are evident in the vertical direction.